Child I - Tasane, Steve (London Faber & Faber Ltd, 2018)
A group of undocumented children with letters for names, are stuck living in a refugee camp, with stories to tell but no papers to prove them. As they try to forge a new family amongst themselves, they also long to keep memories of their old identities alive. Will they be heard and believed? And what will happen to them if they aren't? An astonishing piece of writing that will enchant and intrigue children; perfectly pitched at a 9+ readership.